Ultra rapid fabrication of p-type Li-doped Mg2Si0.4Sn0.6 synthesized by unique melt spinning method. (1st April 2016) - Tang, Xiaodan; Wang, Guiwen; Zheng, Yong; Zhang, Yumeng; Peng, Kunling; Guo, Lijie; Wang, Shuxia; Zeng, Min; Dai, Jiyan; Wang, Guoyu; Zhou, Xiaoyuan
Abstract: In this work, we successfully synthesized p -type Mg2(1-x) Li2x Si0.4 Sn0.6 (x = 0.00, 0.01, 0.03, 0.07, 0.09) samples using a home-made melt spinning system combined with spark plasma sintering. Compared with the samples prepared by a traditional method, the processing time is reduced from typically several days to less than one hour. It is found that the electrical conductivity rises rapidly with the increase of Li content owing to the enhanced carrier density, while the Seebeck coefficient decreases concomitantly to some extent. Meanwhile, Li doping dramatically reduces the thermal conductivity, leading to an enhanced figure of merit ZT 0.58 at 760 K. Graphical abstract: In this work, we successfully synthesized pure p -type Mg2(1-x) Li2x Si0.4 Sn0.6 compounds. Li doping rapidly enhances the electrical conductivity and leads to the highest power factor 1.6 mW K − 2 m − 1, which is much higher than what has been reported in literatures on p-type Mg2 (Si, Sn)-based solid solutions. A ZT up to 0.58 was obtained when x = 0.07.